Autoregulation of ToxR and Its Regulatory Actions on Major Virulence Gene Loci in Vibrio parahaemolyticus - Zhang, Yiquan; Hu, Lingfei; Osei-Adjei, George; Zhang, Ying; Yang, Wenhui; Yin, Zhe; Lu, Renyun; Sheng, Xiumei; Yang, Ruifu; Huang, Xinxiang; Zhou, Dongsheng (Frontiers in Cellular and Infection Microbiology, 2018)
Vibrio parahaemolyticus, the leading causative agent of seafood-associated gastroenteritis, harbors two major virulence gene loci T3SS1 and Vp-PAI (T3SS2 and tdh2). ToxR is a virulence regulator of vibrios. Cell density-dependent transcription pattern of toxR and its regulatory actions on T3SS1 and Vp-PAI have been previously reported, but the detailed regulatory mechanisms are still obscure. In the present work, we showed that the highest transcription level of toxR occurs at an OD600= 0.2- 0.4, which may be due to the subtle repression of ToxR and the quorum sensing (QS) master regulator AphA. We also showed that ToxR is involved in regulating the mouse lethality, enterotoxicity, cytotoxicity, and hemolytic activity of V. parahaemolyticus. ToxR binds to multiple promoters in T3SS1 locus to repress their transcription. In addition, ToxR occupies the multiple promoter DNA regions of Vp-PAI locus to activate their transcription. Thus, ToxR regulates the multiple virulence phenotypes via directly acting on the T3SS1 and Vp-PAI genes. Data presented here provides a deeper understanding of the regulatory patterns of ToxR in V. parahaemolyticus.